Evaluation of Pharmaceutical Services Based on STARKES 2024 Standards - Mohammad Febry Andintias; Opstaria Saptarini; Tri Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The 2024 STARKES accreditation standards emphasize the importance of safe, effective, and quality pharmaceutical services and medication use (Pharmaceutical Services and Rational Drug Use - PKPO). Private hospitals often face challenges in meeting these standards, particularly concerning the storage of medicines and medical consumables. This study aims to evaluate the implementation of PKPO at Hospital X in Demak Regency based on STARKES 2024 standards and to identify priority areas for improvement. A mixed methods approach was employed. Quantitative data were collected through a structured questionnaire based on seven key PKPO indicators. Qualitative data were obtained via direct observations and in-depth interviews with the head of the pharmacy department and related staff. Quantitative data were analyzed using percentage compliance calculations, while qualitative data were analyzed thematically. Priority problems were determined using the Hanlon method. The overall PKPO implementation score at Hospital X was 70.15%, below the minimum accreditation threshold of 80%. The highest scoring indicator was PKPO 1 (Organization) at 87.5%, while the lowest scores were observed in PKPO 5 (Dispensing) at 52.5% and PKPO 3 (Storage) at 60%. The main priority issue identified was the security of pharmaceutical and medical consumable storage (PKPO 3, item 1).